Optimizing the Waterfall Method in Designing an Android-Based Mobile Application for Table Reservation in Coffee Shops - Galih, Rahardian Damar; Widiono, Suyud (Kirana Publisher (KNPub), 2025)
The growth of the coffee shop industry in Indonesia has caused problems in the table reservation system, which is still done manually, such as long queues, uncertainty of seat availability, and poor service. The purpose of this research is to improve service quality by developing an Android-based mobile application that enables table booking and reservation. Requirement analysis, system design, implementation, testing, and maintenance are the stages of the Waterfall Software Development Life Cycle (SDLC) used. Field observations, interviews with managers, and customer questionnaires are the methods used to obtain research data. The implementation results show that the application is capable of making real-time reservations, providing status notifications, and helping managers monitor table capacity. In addition, testing shows that the system can improve customer satisfaction, speed up the reservation process, and reduce queues. Thus, this research found that optimizing the Waterfall method can produce an application that is stable, organized, and relevant to the needs of the contemporary coffee shop industry.